The Compliance of Mask Use to Prevent the Spread of COVID-19 among High School Students in Banda Aceh - Novita Andayani; Sarah Firdausa; Teuku Romi Imansyah Putra; Rezania Razali; Syawqiyyah Salsabyla; Murtaza Murtaza (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: COVID-19 is an air-borne disease caused by the SARS-CoV-2 virus that is spreading the globe. Masks are an attempt to break the chain of transmission of COVID-19. The purpose of this study is to examine the relationship between COVID-19 awareness and the use of masks to prevent the spread of COVID-19 among high school students in Banda Aceh City.Methods: This study is an observational analytic study using a cross-sectional design. The number of samples is 402 students of SMA Negeri Banda Aceh. The subject recruitment used the proportional random sampling technique.Results: This study was carried out from November 5 to November 21, 2020, with research questions distributed via Google Form. The Spearman correlation test was utilized in the statistical study. According to the findings, 69.4% of respondents had good knowledge of COVID-19, and 83.3% of respondents praised the use of masks. Statistical analysis reveals a p-value of 0.000 (p-value of 0.005) and a correlation coefficient of 0.275.Conclusion: There is a modest correlation between Banda Aceh City Public High School students' understanding of COVID-19 and their wearing of masks to prevent COVID-19 transmission.